“Predicción de la dispersión de contaminantes atmosféricos originados en la industria procesadora de balsa INMAIA S.A en la ciudad de Quevedo” - García Vivas, Vicenta Magdalena (2020)
This investigation analyzed the emission control system, dispersion, and different levels of particulate matter concentrations PM10, and PM 2.5 m, CO, SO2 , and NOx which are considered hazardous pollutants from the atmosphere. All of those atmospheric pollutants are emitted from a considerable fixed source located between the rural parishes of San Camilo and San Cristobal. Gaussian dispersion modeling was applied through the SCREEN View program following the guidelines, methods, and parameterization of the USEPA. For this purpose, the meteorological data (multi-year averages) of the study area are used over 31 years, managing to model their direct and indirect relationship with the dispersion of pollutants in the atmosphere and their subsequent deposition. Samples were taken in the fixed source of combustion, and in the ambient air of the direct influence zone of the industry research target industry; soon the data obtained contrasted with the current environmental regulations, and it was analyzed with some statistical and geostatistical analysis being able to define the operating conditions of the timber industry within the permissible limits established in the standard. A survey was applied to capture the perception of the inhabitants within the direct buffer (200 meters), managing to identify that the inhabitants consider the industry as a source of mainly material particles and soot, which cause the main affectations, especially to those located to the south, and the north of the company. The maximum concentrations obtained with the SCREEN VIEW program, for all pollutants, were Total particles 4.21 g/m3 , CO 329.4 g/m3 , NOx 6,293 g/m3 , SO2 4,526 g/m3 , all distances of 170 meters in the atmospheric stability category D. The findings also exposed that the inhabitants of the east side of influence feel affected by an additional source of the smoke and bad odors. Therefore, these results suggest future studies to know in deep the factors of decrease in air quality in the area. Keywords: Modelling, Gaussian plume, air quality, Screen View, air pollutants, particulate matter, PM 10, PM 2.5m, Biomass Combustion, atmospheric stability